Identification and characterization of two repetitive non-variable antigens from African trypanosomes which are recognized early during infection - Muller, N.; Hemphill, A.; Imboden, M.; Duvallet, G.; Dwinger, R.H.; Seebeck, T. (Cambridge University Press, 1992)
The present paper describes two repetitive proteins representing common antigens of African trypanosomes which are non-variant and which are recognized early in infection by the host immune system. These antigens were identified by their ability to immunoreact with bovine serum taken during the early phase of a cyclic trypanosomal infection. Screening of a cDNA library fromT. b. gambiensewith such early infection serum identified a protein which contains a repetitive motif consisting of 68 amino acid repeat units (GM6). Immunofluorescence and immunogold electron microscopy revealed that GM6 is located on fibres which connect the microtubules of the membrane skeleton with the flagellum. A second repetitive antigen detected by this serum is MARP1 (microtubule-associated repetitive protein 1), a protein previously characterized in this laboratory as a high-molecular weight component of the membrane skeleton, which consists of more than 50 tandemly repeated, near-identical 38 amino acid repeat units. Beta-galactosidase fusion products of both proteins demonstrated a strong immunoreactivity with sera fromT. b. bruceiandT. congolense-infected cattle. The result from this preliminary immunological evaluation indicates a high immunodiagnostic sensititivy (90%) of the two recombinant antigens which make them interesting candidates for immunodiagnosis of trypanosomiasis in cattle.